Dependence of the Future Elderly on Private Cars: A Case Study in Beijing - Jian, Meiying; Shi, Jing; Liu, Yang (Promet - Traffic&Transportation, 2018)
With the aging of population in the world, understanding the travel demands of the elderly is important. In China, the aging society is in the process of forming. Meanwhile the urban motorization has just started. The aim of this paper is to investigate the dependence of the future elderly on private cars. The data used here come from a stated preference (SP) survey of the young and middle-aged residents in the capital of China, Beijing. The influencing factors on the car ownership and mode choices of the future elderly are analysed based on the ordered logit model and MNL model, respectively. The effect of uncertainty in respondents’ statements on the car usage has been also investigated. The results show that the future elderly in Beijing become increasingly dependent on private cars. It is also found that younger people have higher propensities to own private cars and to make use of driving after the age of 65. Moreover, improving public transport services contributes to an increased ridership of public transport by the future elderly. The findings in this paper can provide valuable references for the aging society when making transport policies in Beijing.